Development of a Quality Evaluation Model for Village Government Financial Reporting in Boyolali Regency, Center Java, Indonesia - Mohamad Mahsun; Junaidi Junaidi; Sumiyana Sumiyana; Nurdiono Nurdiono; Suparmono Suparmono (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to evaluate the quality of financial reporting in village administrations, which is crucial for effectively managing village funds in Indonesia. Methodology: In 2020, this study involved 164 participants and employed a mixed-methods approach combining quantitative and qualitative techniques. The financial reporting quality model classifies data into three categories: Cluster A (audit-ready), Cluster B (needing oversight), and Cluster C (requiring intervention). Results: The quality assessment model for village financial reporting can be categorized into three clusters: Cluster A, readiness for audit (51%); Cluster B, need for supervision (33%); and Cluster C, need for assistance (16%). Conclusions: This study highlights the importance of good governance in village financial reporting, emphasizing the need for accountability and transparency. The research proposes a quality assessment model that categorizes villages into three clusters: audit-ready (51%), requiring supervision (33%), and needing assistance (16%). Adequate human resources and adherence to regulatory standards are key factors in improving the quality and reliability of village financial reports. Limitations: This research was conducted during a period when standardized accounting principles for village finances have not yet been established, which represents a key limitation. High-quality financial statements are characterized by compliance with applicable accounting standards. The suboptimal quality observed in the financial statements of many villages is likely attributable to the absence of specific accounting standards governing village financial reporting. Contribution: Theoretically, this study seeks to identify practical concepts for managing village finances. The proposed financial reporting quality model offers a framework for improving the quality of village financial reports while enhancing the understanding of financial reporting practices in village governments, particularly in Boyolali Regency.